2016
DOI: 10.1080/15487768.2016.1197862
|View full text |Cite
|
Sign up to set email alerts
|

Sorting it out: Eliciting consumer priorities for recovery in supportive housing

Abstract: Objective This study aims to understand participant priorities in their personal recovery journey and their perspectives of recovery domains. Methods A card sort data gathering technique was employed to elicit priorities in recovery from consumers in supportive housing programs serving formerly homeless adults with severe mental illnesses in New York City. Participants (N=38) were asked to sort 12 cards printed with recovery domains in order of importance and describe the meaning attached to each domain. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Consistent with past research examining recovery among people with mental illness who have histories of homelessness (e.g., Choy-Brown et al, 2016;Padgett et al, 2012Padgett et al, , 2016, participants in this study reported experiencing many adversities beyond their mental health and housing, such as substance use problems, trauma and victimization, chronic medical conditions, incarceration, sex work, social isolation and loneliness and food insecurity. As such, participants often discussed recovery more broadly, holistically considering how services affected their various challenges.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with past research examining recovery among people with mental illness who have histories of homelessness (e.g., Choy-Brown et al, 2016;Padgett et al, 2012Padgett et al, , 2016, participants in this study reported experiencing many adversities beyond their mental health and housing, such as substance use problems, trauma and victimization, chronic medical conditions, incarceration, sex work, social isolation and loneliness and food insecurity. As such, participants often discussed recovery more broadly, holistically considering how services affected their various challenges.…”
Section: Discussionsupporting
confidence: 81%
“…Through the use of a Q-sort activity, the authors of this study were able to operationalize the subjectivity within a group of persons crafting a life toward mental health and well-being in three communities within northeast Ontario. Another study by Choy- Brown, Pagdett, Smith, and Tiderington (2016) identified securing housing as a foundation for physical and mental health. The results of this study identify the four discrete viewpoints about priorities for supportive housing.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the context of caregiving, family perspectives on recovery have largely been ignored, despite family being recognized as an important ‘recovery domain’ (Choy-Brown, Padgett, Tran Smith, & Tiderington, 2016). Our study contributes to current knowledge by utilizing CHIME to map families’ views on personal recovery and to housing literature by exploring families’ perspectives on the connections between supported housing and recovery.…”
Section: Introductionmentioning
confidence: 99%